Obesity in School-age Children and the Role of Community Health Nurse - Pattana, Kancharee; Thongsri, Praleena (Vajira Medical Journal : Journal of Urban Medicine, 2019)
Currently, obesity in school-age children is likely to increase continuously. It is one of the important problems of public health that needs to be solved quickly. Because obese school children are more at risk of other serious diseases than children with normal body weight. School-age children are often induced to consume foods that are high in energy and have less exercise. Causing imbalance of energy metabolism and accumulation of fat in the body until obesity. Affecting the health of children both physically, mentally and socially. Therefore, community health nurses play an important role in creating health for school-age children. By assessing and screening health conditions, problem diagnosis, nursing planning and evaluation. Including being an educator as a consultant to increase the potential of children, parents, schools and communities in changing food consumption behaviors and proper exercise to control body weight to normal weight for prevent complications that may follow in the future. It is also a researcher to create new knowledge in community health development and continuously coordinate to create cooperation in the community.